Role of fibreoptic bronchoscopy in the diagnosis of mycobacterial diseases. Issue 4 (April 1983) - Funahashi, A; Lohaus, G H; Politis, J; Hranicka, L J
Abstract : From January 1976 to December 1981 mycobacteria were recovered for the first time from the respiratory tract of 179 patients. Twenty-three patients had undergone fibreoptic bronchoscopy during initial investigation after three or more expectorated sputum specimens were negative for acid-fast bacilli. Three of these patients had nodular lesions on the chest radiograph and the diagnosis of mycobacterial disease was made only after thoracotomy. In the remaining 20 patients bronchial brushings yielded a positive culture in 19, while bronchial brushing was negative in one patient in whom culture of sputum before bronchoscopy had been positive. In eight of these 19 patients (group A) bronchial brushing was the only source that gave a positive result from culture, while in 11 patients (group B) both bronchial brushing and prebronchoscopy sputum yielded positive cultures. When these two groups were compared no difference was seen in their clinical presentation or radiographic findings but there was a notable difference in the quality of the presentation or radiographic findings but there was a notable difference in the quality of the prebronchoscopy sputum. Six of eight patients in group A had poor prebronchoscopy sputum, while 10 of 11 in group B had good prebronchoscopy sputum. It is concluded that, if a patient is unable to produce sputum or is able to produce only a poor specimen, fibreoptic bronchoscopy may be a useful means of obtaining additional material for culture.